WIRELESS DATA TRANSMISSION AND ACTUATION OF FLOW CONTROL PROCESS - Abdullah, Siti Nur Ashikin (2017)
WSN technology has been widely used for plant process system over a past ten years and brings more advantages in term of installation and maintenance cost compared to traditional wired system. However, WSN only involved monitoring process. This project is to implement Wireless Networked Control System (WNCS) from sensor to controller and feedback controller to control valve in a flow control loop. WNCS will be implemented using National Instrument (NI) wireless equipment. Data transmission in WNCS will be transmitted using either ZigBee or Wi-Fi. In this project, the WirelessDAQ for Analog Input(AI) module and Analog Output (AO) module are tested by using current injector Beamex. The WirelessDAQ able to read and display 4 to 20 mA currents by using LAN cable and wireless transmission. Next step is to test the performance of WirelessDAQ AI module over ZigBee and Wi-Fi wireless communication network by observing the controller performance, data transmission range and power management.